Western U.S. multistate research project on "water movement in soils": A retrospective. Issue 1 (22nd December 2022) - Hopmans, Jan W.; Green, Timothy R.; Young, Michael H.
Abstract: To prioritize agricultural research in the United States and to improve its competitiveness globally, Multistate Research Funds (MRFs) were set aside under the Research and Marketing Act of 1946. To implement the act, Agricultural Experiment Station (AES) Directors in the western United States met regularly to evaluate, fund, and review multistate research projects (MRPs), with membership of AES scientists named by the Technical Committee. This article highlights the history of research collaboration in the soil and vadose zone scientific community that was initiated in the western United States. The scientific interactions that started in 1958 with 10 scientists in western land‐grant universities and the USDA to address "Water Movement in Soil" have grown in membership and scope through successive 5‐yr projects. We highlight the value of such collaboration and the scientific advances in soil science and vadose zone hydrology. Core Ideas: The Multistate Research Project on "Water Movement in Soils" is one of the oldest projects of its kind in the United States. The research results have led to significant advances in soil and vadose zone sciences. This letter provides a retrospective of this successful collaborative project.